2020
DOI: 10.1080/00324728.2020.1775873
|View full text |Cite
|
Sign up to set email alerts
|

Children’s education and parental old-age health: Evidence from a population-based, nationally representative study in India

Abstract: Previous research has documented intergenerational transmission of human capital from children to parents. Less is known, however, about heterogeneity in this 'upward transmission' in low-resource settings. We examine whether co-resident adult children's education is associated with improved health among older parents in India, using nationally representative data from the 2014 Indian National Sample Survey. Parents of children with tertiary education had a lower probability of reporting poor health than paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
(85 reference statements)
2
15
0
Order By: Relevance
“…However, it is possible that the link runs in the opposite direction as well [ 18 ]. Although the positive impact of education on human health has been well established in the literature, the causal effect of offspring education on the health of the older population has only recently received attention [ 12 , 16 , 17 , 32 , 40 ]. Our study expanded on recent work assessing the relationship between offspring education and parents’ health inequality by providing causal evidence in China [ 17 ] in a number of important ways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is possible that the link runs in the opposite direction as well [ 18 ]. Although the positive impact of education on human health has been well established in the literature, the causal effect of offspring education on the health of the older population has only recently received attention [ 12 , 16 , 17 , 32 , 40 ]. Our study expanded on recent work assessing the relationship between offspring education and parents’ health inequality by providing causal evidence in China [ 17 ] in a number of important ways.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of supporting the elderly falls more heavily on the one child. As a key component of intergenerational connections, changes in living arrangements may cause changes in the relationship between offspring education and parents’ health [ 32 ]. Thoma et al [ 32 ] found that in India, the education of children who live with their parents is significantly related to health improvements in the elderly.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The extent to which this younger generation shares its increased resources with their parents, however, remains largely unknown. More than a dozen studies have reported a positive correlation between children’s human capital and parental health, including in China, 13 India 14 and South Africa. 15 Given the large number of potential factors (such as genetic traits) that may confound the relationship between children’s human capital and parental health, however, these correlations are difficult to interpret and are unlikely to identify causal effects of educational opportunities provided to children.…”
Section: Introductionmentioning
confidence: 99%